1989
DOI: 10.1111/j.1476-5381.1989.tb11882.x
|View full text |Cite
|
Sign up to set email alerts
|

Na+‐K + pump activity in rat peritoneal mast cells: inhibition by extracellular calcium

Abstract: 1 Pure populations of rat peritoneal mast cells were used to study cellular potassium uptake. The radioactive potassium analogue, 86rubidium, was used as a tracer for potassium for measurements of the activity of the cellular potassium uptake process. 2 The ouabain-sensitive and the ouabain-resistant potassium (86rubidium) uptake of mast cells incubated in the presence of calcium, 1 mmol 1-, were very low, 52 and 147 pmol per 106 cells minm -. 3 Calcium-deprivation of the cells uncovered a large capacity ouaba… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

0
19
0

Year Published

1990
1990
1995
1995

Publication Types

Select...
7

Relationship

1
6

Authors

Journals

citations
Cited by 33 publications
(19 citation statements)
references
References 17 publications
0
19
0
Order By: Relevance
“…The initial uptake value was not influenced by the presence of magnesium. The high level of K+(86Rb')-uptake is due to cellular accumulation of sodium during cell preparation (Knudsen & Johansen, 1989a). The rapid decrease after 10 min exposure of the cells to magnesium at 370C may be explained by an outward transport of sodium by the pump mechanism having a higher rate than the concomitantly inward transport of sodium.…”
Section: Discussionmentioning
confidence: 99%
See 2 more Smart Citations
“…The initial uptake value was not influenced by the presence of magnesium. The high level of K+(86Rb')-uptake is due to cellular accumulation of sodium during cell preparation (Knudsen & Johansen, 1989a). The rapid decrease after 10 min exposure of the cells to magnesium at 370C may be explained by an outward transport of sodium by the pump mechanism having a higher rate than the concomitantly inward transport of sodium.…”
Section: Discussionmentioning
confidence: 99%
“…By interpolation it may be observed that half maximal decrease in the pump activity occurred in the presence of 1.8 mm magnesium, 1.2 mm barium and 0.7mm strontium. These values may be compared with the concentration of calcium, 0.2mm, causing half maximal inhibition under identical experimental conditions (Knudsen & Johansen, 1989a). In contrast, lanthanum ion 1 uM caused the same degree of inhibition of the pump as 1 mm calcium, but the inhibition was not further increased by incubation of the cells with both calcium and lanthanum ( Figure 5).…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…The rats were killed by decapitation under light ether anaesthesia. The mast cells were isolated by differential centrifugation of mixed peritoneal cells in a self-generating gradient of Percoll as previously described (Knudsen & Johansen, 1989a release) was added to the cell samples to give a final volume of 0.5 ml during the incubation. After 3-10 min (see legends to figures), the incubation was terminated by addition of ice-chilled Krebs-Ringer solution 9.5 ml (K+(86Rb+)-uptake) or 1.75 ml (histamine release) to the cell suspensions.…”
Section: Isolation Of Mast Cellsmentioning
confidence: 99%
“…Recently, it has been shown that the plasma membrane of the rat peritoneal mast cell contains a Na+/K+-pump (Knudsen & Johansen, 1989a). The pump activity is inhibited by calcium (Knudsen & Johansen, 1989a,b) and other divalent cations .…”
Section: Introductionmentioning
confidence: 99%